(3GdYQhV GdHGQY HGdENJUGQ GdLGeYs - (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdSYOj GdUbdj GdeUQj, GdeYQha H GHf GdbWGY,J (B515 (3g` s ((3eMeO Hf eMeO Hf eMeO Hf OGhO GdUfgGLi GHf BLQhe s)
(3ChdgG (B:s
(3GdMeO ddg MeO eYJQa HPfHg EYde Cf GdYQhV Yde hVY deYQaI ChRGf TYQ GdYQH s
(3BNQgG (B:s
(3gPG LedI eG CgedJ GdYQH ef GdCHfjI , hde jCJ dgG ajg TYQ GdHJg GfJgi EdfjG CKHJg ai gPG GdeNJUQ hEdi Gddg GdQZHI hYdjg GdEJcGd s
(3GdfSNI HgG MhGTs
(3HYO GdcJGH JbjjOGJ ai (B3 (3hQbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1134s
Keywords: (3GdHdGZIs